Essential infantile esotropia - Ljubic, Antonela; Trajkovski, Vladimir (Лекарска комора на Македонија, 2014)
Aim : To determinate the prevalence of congenital infantile esotropia (ETI) in strabismic population with Down syndrome versus strabismic control group from the general Macedonian population. To present subject age, sex distribution, maternal age and spherical equivalent in each of the two analyzed groups. Patients and methods: Population- based retrospective case- control study was conducted in which a study group (52) (strabismic group with Down syndrome) and a control group (257) (strabismic group of the general healthy population of children and young adults) were analyzed. Each subject underwent strabismic examination and calculated spherical equivalence based on refractive status in short-term cycloplegia. Statistical processing included the preparation of percentages of structure and average value. Results: Out of a total of 52 children and young adults with Down syndrome and strabismus group, 4 subjects showed the presence of ETI (4/52) 7.7%. Out of a total of 257 children and young adults without Down syndrome from healthy general population, 13 subjects showed the presence of ETI (13/257) 5.0%. The average value of the spherical equivalent in the ETI Down syndrome strabismus group was +1.69 D, while the average value of the spherical equivalent in the ETI general population control group was +2.20 D Conclusion: The prevalence of ETI in the Down syndrome strabismic population was 7.7% versus 5.0 % in general strabismic population . The spherical equivalent results in our study showed a small hypermetropia, as already published studies on refractive status in ETI.
Есенцијална инфантилна есотропија
Keywords: essential infantile esotropia, prevalence, spherical equivalent, treatment